1996
DOI: 10.1113/expphysiol.1996.sp003930
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic hydrogen ion buffering in rat CNS neurones maintained in culture

Abstract: SUMMARYThe intrinsic proton buffering power (/1) of individual rat hippocampal and neocortical neurones maintained in culture has been investigated using the fluorescent dye 2',7'-bis(carboxymethyl)-5,6-carboxyfluorescein) (BCECF). The steady-state intracellular pH (pH,) was estimated to be 7.03 + 0.04 (n = 22) in Hepes-buffered media and /3i estimated from the addition and removal of weak bases was ca 10 mM (pH unit)-' at pHi values near to 7. Estimates of /#j made from butyric acid challenges were inconsiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…Mean total buffering power of four cells subjected to these two conditions was estimated to be 6*03 mm (pH unit)-1 at a mean pHi of 7-25 in Cl--containing media and 7.45 mM (pH unit)-1 at a mean pHi of 7 24 in Cl--free media. We have already reported that values of intrinsic buffering power measured from cells bathed in Na+-containing and Na+free solutions were not significantly different (see Amos & Richards, 1996) and estimates of AT under the same conditions also showed no significant difference (n = 5 cells). Estimates offT in the presence of acetazolamide It has been suggested (Thomas, 1976) that the presence of carbonic anhydrase (CA) is necessary for the CO2-HCO3system to work to its full potential.…”
Section: Estimates Of / Using Nii4clmentioning
confidence: 74%
See 4 more Smart Citations
“…Mean total buffering power of four cells subjected to these two conditions was estimated to be 6*03 mm (pH unit)-1 at a mean pHi of 7-25 in Cl--containing media and 7.45 mM (pH unit)-1 at a mean pHi of 7 24 in Cl--free media. We have already reported that values of intrinsic buffering power measured from cells bathed in Na+-containing and Na+free solutions were not significantly different (see Amos & Richards, 1996) and estimates of AT under the same conditions also showed no significant difference (n = 5 cells). Estimates offT in the presence of acetazolamide It has been suggested (Thomas, 1976) that the presence of carbonic anhydrase (CA) is necessary for the CO2-HCO3system to work to its full potential.…”
Section: Estimates Of / Using Nii4clmentioning
confidence: 74%
“…(1) The Hender-son-Hasselbalch equation is not valid in this situation. Since application of the Hendersor I -lasselbalch equation gave sensible and consistent estimates of intrinsic buffering when exogenous weak acids and weak bases were added and removed or when P(, was varied from ca 18 to 36 mmHg (see Amos & Richards, 1996), there seems every reason to believe it to apply in this system. In any event, such an explanation would raise as maLny difficulties as it would resolve.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations